THE PROPHET MUHAMMAD’S TEACHING METHODS AS A STRATEGY FOR DERADICALIZATION IN ISLAMIC EDUCATION - Khoirul Jazilah; Justsinta Sindi Alivi; Dewi Mariatus Solikah (MIYAH: Jurnal Studi Islam, 2026)
This study examines prophetic pedagogy derived from the educational practices of Prophet Muhammad SAW as a strategic framework for strengthening religious moderation and countering radicalism in contemporary Islamic education. Using a qualitative library research method, the study analyzes classical Islamic sources and recent scholarly publications from 2021–2025 to identify relevant pedagogical principles and their contemporary applications. The findings show that prophetic pedagogy is grounded in compassion (rahmah), wisdom (hikmah), justice (‘adl), exemplary conduct (uswah), and dialogical interaction. These principles are closely aligned with humanistic and constructivist educational approaches that promote inclusive learning, critical reflection, and ethical responsibility. The study further reveals that the integration of prophetic pedagogical values into Islamic Religious Education can reduce learners’ vulnerability to radical narratives by encouraging balanced religious understanding and peaceful social engagement. The significance of this research lies in its contribution to reconceptualizing prophetic pedagogy as a systematic educational framework rather than merely historical teaching practices. Practically, the results provide guidance for educators, curriculum developers, and policymakers in designing moderation-oriented learning models rooted in Islamic values. The study concludes that prophetic pedagogy remains highly relevant as a transformative strategy for promoting peace, social cohesion, and Islam as rahmatan lil ‘alamin in contemporary society